Aplicação da batimetria multifeixe para definição da morfologia detalhada do fundo marinho ao largo da laguna de Araruama e Arraial do Cabo - RJ - Simões, Isabel Cristina Vendrameto Peres (2008)
This study was carried out on the continental shelf offshore Araruama lagoon and Arraial do Cabo town, between 45 and 100 meters water depth. The bottom morphology is correlated to sediment dynamics and sea-level in order to understand sedimentary evolution. Data utilized in this research are bathymetric data from conventional and multibeam echo sounders, bottom sediment information, shallow seismic profiles and backscatter strength. Morphological features identified and described in this study are: - an escarpment southeast off Cabo Frio island interpreted as an actual progradation front of fine sediments from northeast to southwest associated with northeast sediment drift; - a concave bathymetric depression with reduced sedimentation used as passage by upwelling and down welling currents; - a fan like sand deposit built during bad weather conditions, with southwest winds pilling up water against continent; - a scour along the east side of Cabo Frio island indicating presence of a deep flow from northeast; - a terrace and a beach rock with presumed ages of 11.000 and 9.000 B.P., and - sand ridges at depths of 100 meters built by storm waves from southwest during low sea-level. A model for sediment dynamics is proposed for fair and bad weather conditions